(Z)-2-(Bromomethyl)-3-(hydroxymethylene)-7-methoxy-5-methyl-2-(tribromomethyl)-4-chromanone - Chein-Chung Lee; Yen-Ku Wu (Molbank, 2025)
An attempt to achieve the deprotonative bromination of a 2-methyl-3-formyl-chromenone with tetrabromomethane led to an unexpected bromo-tribromomethylation product. We report the synthesis and characterization of the title compound.